2017
DOI: 10.1149/2.021706jss
|View full text |Cite
|
Sign up to set email alerts
|

LiF Doping of C60Studied with X-ray Photoemission Shake-Up Analysis

Abstract: We report our investigation of the chemical doping mechanism induced by LiF interaction with fullerene thin films. High resolution Xray photoelectron spectroscopy of the C1s shake-up satellites and F1s main core level, supported by density functional calculations, suggest the formation of a charge transfer complex between covalent LiF monomers and dimers and C 60 . This interaction was observed in both LiF/C 60 and C 60 /LiF depositions, suggesting that some charge transfer complexation can occur in these syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…These were observed at 1.2 eV below and 1.3 eV above the respective ester CO and C–O–C peaks. As an interesting note, Turak et al deposited LiF onto in situ-evaporated C 60 and observed a charge complex formation occurring via the F 1s and C 1s conjugated π states in the fullerene cage; a high binding energy shoulder was present in the F 1s XP spectrum, and the conjugated π states were seen to increase in intensity. The air-curing of the PCBM and consequential oxidation in the present work could possibly have had an impact on the observed differences in LiF upon deposition on the fullerene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were observed at 1.2 eV below and 1.3 eV above the respective ester CO and C–O–C peaks. As an interesting note, Turak et al deposited LiF onto in situ-evaporated C 60 and observed a charge complex formation occurring via the F 1s and C 1s conjugated π states in the fullerene cage; a high binding energy shoulder was present in the F 1s XP spectrum, and the conjugated π states were seen to increase in intensity. The air-curing of the PCBM and consequential oxidation in the present work could possibly have had an impact on the observed differences in LiF upon deposition on the fullerene.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the concentration depth profiles of the components across the interface should also be determined to check for diffusion. There are many reports in the literature that have determined changes of the electronic structure for the near-surface area upon deposition of LiF onto organic interface materials ,,, and the LiF layer formation on various organic layers, ,,,, but none as yet have addressed the changes in the electronic structure of the salt/organic layer interface upon salt deposition, whilst monitoring the chemical changes with salt deposition and also determining the vertical distribution of the salt.…”
Section: Introductionmentioning
confidence: 99%
“…The observed change in the LiF crystal texture was not consistent with that observed under other irradiation conditions [55] and, thus, warrants further study. The photoemission spectra of the damaged sample showed that the C 1s feature from DIP was intact, with only a slight shoulder at a higher binding energy, which may be consistent with F C bonding [56], but this is inconclusive.…”
Section: Resultsmentioning
confidence: 94%
“…After an electron is emitted during the photoionization process, valence electron will rearrange. When the conjugated ladder structure is formed, the valence electron from the highest occupied molecular orbital (HOMO) probably transits to an unoccupied lowest unoccupied molecular orbital (LUMO) [35], resulting in π-π * shake-up [36]. Besides, the gap to Femi energy level also decreases [37], so that multi valence electrons can transit to empty states in Femi energy level, which leads to asymmetric tailing.…”
Section: Formation Of Conjugated Ladder Structures In Airmentioning
confidence: 99%